Examining the role of physical activity in managing hypertension among India’s older population - Anshika Singh; Aditya Singh (National Geographical Journal of India, 2025)
Hypertension, a chronic condition and major global health burden, is a leading cause of strokes, heart disease, vascular disorders, and kidney disease. Its prevalence is rising due to aging populations and increased exposure to lifestyle risks such as poor diets and inactivity. Regular exercise helps avoid and control chronic conditions like heart disease, diabetes, hypertension, and stroke. This study examines the demographic and socioeconomic factors influencing the association among physical activity and hypertension among adults aged 60 and above in India. Drawing cross-sectional data from wave 1 of Longitudinal Aging Study in India (LASI) ,2017-18. The analysis includes sample of 27,176 individuals. The association between physical activity and hypertension was evaluated using logistic regression analysis, and the Population Attributable Factor was computed to examine the percentage of instances of hypertension that might be avoided by adhering to prescribed levels of physical activity. The results indicated that individuals with inadequate physical activity had 23% higher odds of hypertension (AOR: 1.14, p < 0.001). The analysis suggested that sex, currently working status, self-rated health, household consumption expenditure, education, place of residence, need supportive aid for activities of daily living, and bodyweight were significant factors associated with hypertension. The PAF estimate of 0.0833 (95% Confidence Interval: 0.6665, 0.0998) suggests that 8.3% of hypertension cases could be reduced by improving from inadequate to adequate levels of physical activity. Hypertension is an increasing public health concern, especially among older adults with inadequate physical activity. Targeted interventions, including lifestyle awareness programs and screening for high-risk groups, may effectively reduce hypertension risks.